Annual Plan Proposals 1987-88 Government of Kerala - Planning Commission (Planning Commission, 1986)
The size of the State’s Seventh Five Year Plan is Rs. 2100 crores. While formulating the seventh plan the objectives and strategy outlined in the Seventh Five Year Plan of India, the recommendations 1 of the State High Level Committees and the suggestions of the various Working Groups of the Planning Commission were given due consideration. Care was taken to ensure that the spillover commitments, commitments on externally aided projects and the State’s share of Centrally sponsored schemes were adequately provided for. The outlay required for completing the ongoing works programmes which had a reasonable prospect of being completed during the Seventh Plan was fully provided.
State Planning Board Trivandrum